Influence of tree plantations on physico-chemical properties and microflora of soil - Chandra, K.K.; Kumar, Niraj; Verma, Avinash; Saxena, A.K. (Indian Journal of Agroforestry, 2020)
Tree plantations of twelve different species were established in degraded oxisols for almost two decades by the State Forest Research Institute at Jabalpur, Madhya Pradesh (India). The present study was conducted to evaluate the potentialities of these plantations for the restoration of degraded oxisols. Results showed a marked improvement in biochemical characteristics of soil by increasing the water holding capacity, porosity and organic matter. Soil nitrogen was improved by 39.8%, phosphorus 42.19%, potassium 37% and calcium 52% under tree plantations of 19-23 years age compared to the unplanted soil. The copper content was 83.7% greater, while Iron, Magnesium, and Zinc were about 52% to 58.5% greater due to tree plantations. It was found that Eucalyptus citrodora, Dalbergia sissoo and Bambusa arundinacea were more efficient than other tree species in rehabilitating oxisols. Under these trees the content of organic matter, nutritional properties and microbial populations were greater than under other plantations. Soil microbial activity was enhanced up to 2.9 fold due to accumulation of humus through organic matter. Mycorrhizal density also improved over 5 times in plantation than unplanted soil.